Understanding the Compositional Variability of the Major Components of Hydrothermal Plumes in the Okinawa Trough. (4th April 2018) - Zeng, Zhigang; Wang, Xiaoyuan; Chen, Chen-Tung Arthur; Qi, Haiyan
Abstract : Studies of the major components of hydrothermal plumes in seafloor hydrothermal fields are critical for an improved understanding of biogeochemical cycles and the large-scale distribution of elements in the submarine environment. The composition of major components in hydrothermal plume water column samples from 25 stations has been investigated in the middle and southern Okinawa Trough. The physical and chemical properties of hydrothermal plume water in the Okinawa Trough have been affected by input of the Kuroshio current, and its influence on hydrothermal plume water from the southern Okinawa Trough to the middle Okinawa Trough is reduced. The anomalous layers of seawater in the hydrothermal plume water columns have higher K +, Ca 2+, Mn 2+, B 3+, Ca 2+ /S O 4 2 -, and Mn 2+ /Mg 2+ ratios and higher optical anomalies than other layers. The Mg 2+, S O 4 2 -, Mg 2+ /Ca 2+, andS O 4 2 - /Mn 2+ ratios of the anomalous layers are lower than other layers in the hydrothermal plume water columns and are consistent with concentrations in hydrothermal vent fluids in the Okinawa Trough. This suggests that the chemical variations of hydrothermal plumes in the Tangyin hydrothermal field, like other hydrothermal fields, result in the discharge of high K +, Ca 2+, and B 3+ and low Mg 2+ andS O 4 2 - fluid. Furthermore, element ratios (e.g., Sr 2+ /Ca 2+, Ca 2+ /Cl − ) in hydrothermal plume water columns were found to be similar to those in average seawater, indicating that Sr 2+ /Ca 2+ and Ca 2+ /Cl − ratios of hydrothermal plumes might be useful proxies for chemical properties of seawater. The hydrothermal K +, Ca 2+, Mn 2+, and B 3+ flux to seawater in the Okinawa Trough is about 2.62–873, 1.04–326, 1.30–76.4, and 0.293–34.7 × 10 6 kg per year, respectively. The heat flux is about 0.159–1, 973 × 10 5 W, which means that roughly 0.0006% of ocean heat is supplied by seafloor hydrothermal plumes in the Okinawa Trough.